From Ambition to Execution : Policies in Support of Sustainable Development Goals - Fabrizio, Stefania; Garcia-Verdu, Rodrigo; Pattillo, Catherine; Peralta-Alva, Adrian (Washington, D.C. : International Monetary Fund, 2015)
The formal launch of the Sustainable Development Goals (SDGs) sets the global development agenda through 2030, placing significant emphasis on promoting social and environmental sustainability alongside economic growth and poverty reduction. Meeting the SDGs will require actions across a wide range of areas by both national governments and the international community. This paper examines the types of policies that developing countries will need to implement to foster economic transformation, to promote economic and social inclusion, and to meet key environmental objectives. Reducing inequality, achieving gender equity, and pricing energy and water resources appropriately receive particular attention.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet